The Effect of Liquid Organic Fertilizer Concentration on Growth and Production of Pakcoy Mustard (Brassica rapa L.) - Muhammad Irfan Hakim; Andriani Eko P (Procedia of Engineering and Life Science, 2021)
This research aims to find out the influence of liquid organic fertilizer concentration on the growth and production of mustard pakcoy (Brassica rapa L.). The research was conducted in Jiken village, Tulangan District, Sidoarjo Regency and plant physiology laboratory of Muhammadiyah University of Sidoarjo in July to September 2020. This research using RandomIzed Group Design (RAK) was compiled in a single factor, namely the concentration of liquid organic fertilizer with a level of 25%, 50%, 75% and repeated 3 times so that there are 30 units of experiments. The observed variables are: plant height (cm), leaf area (cm2), number of leaves (strands), wet weight (grams), antioxidant activity (ppm). The data was analyzed using ANOVA followed by BNJ test at 5% test level. The results showed no noticeable influence on the variable height of the plant and the area of the leaves. In variable number of leaves and wet weight there is a noticeable influence on the treatment of liquid organic fertilizer concentration 75% application as much as 4 times at the observation age of 35 days with the average yield of the number of leaves (17.33 strands) and wet weight (92 grams). Antioxidant activity tests showed the best results in the control treatment with the lowest value (174,779 ppm) because the lower the IC50 value, the better the antioxidant activity.